Evaluation Of Light Transmitting Ability of Various Aesthetic Posts and Its Effect on Push-Out Bond Strength of Dual Cure Resin Cement - Vanaki, Shreya Shreenivas; R Vinaychandra, R Vinaychandra; Varghese, Ajil Aji; Dhamodaran, Thokala; Jaichander, Mrinalini; Ranjith, K (Journal of Neonatal Surgery, 2025)
Endodontically treated teeth with coronal structure loss often require posts and cores for retention. With rising demand for aesthetic restorations, non-metallic fiber posts have become popular due to their mechanical properties and light transmission ability. However, studies show inadequate polymerization of resin cement, especially in the middle and apical regions of root canals. Dual-cured resin cements help overcome this issue, but their degree of conversion (DC) decreases without sufficient light exposure, leading to reduced push-out bond strength due to the presence of residual monomer. Optimizing polymerization, proper cementation techniques, and ensuring adequate light intensity exposure are essential for the longevity and success of post-retained restorations..